Make no bones - Elkins, Aaron J. (Elkins, Aaron J. Gideon Oliver novels, 1991)
This Gideon Oliver mystery takes place at a forensic anthropoligists' conference, and the site where years before two of their own met with a terrible accident. Whose bones has Gideon found? And who doesn't want the answer?